Causality Analysis Between Human Development Index and Economic Growth in Regencies/Cities in NTT Province - Banase, Marianus Antonius Deo Datus; Loda, Adelheid Elisabet; Gamatara, Maksimilianus Paulus Jati (Jurnal Ilmu Ekonomi JIE, 2026)
This study analyzes the causal relationship between the Human Development Index (HDI) and economic growth, both in the long and short term. The study covers 22 districts/cities in East Nusa Tenggara Province (NTT) and spans the period 2019 to 2023. The study employs a quantitative, causal–explanatory approach to examine the causal relationship between the HDI and economic growth at the regency/city level in NTT. Data were analyzed using panel data techniques to test the causal relationship between the two variables. The results indicate that, according to the unit root test, the HDI and economic growth variables are stationary. The cointegration test indicates a long-term relationship between HDI and economic growth. However, the two-way causality test did not find evidence of a short-term causal relationship between the two, which is thought to be influenced by other factors such as population growth dynamics and other structural variables not included in the model.